Efektivitas Penggunaan Media Pembelajaran SAC Berbasis Android pada Materi Sistem Pencernaan - Kurniawan, Dede; Tanjung, Indayana Febriani (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The purpose of this study is to test the success of Android application media and see the results of practice in the digestive system module of school people. The type of study used is pre-experimental. This study used the concept of one group of pretest-posttest. For research, the activity submitted is the use of Android application media in the human digestive system module. This survey was conducted at Madrasah Nurul Hakim tembung. Research Point Class XI students, a total of 27 students. I took a pre-test before treatment and a total of 50 post-tests after treatment. Analysis of the increase in exercise results was performed using the t-test and the n-gain method. The t-test is used to determine if the increase in training effort is significant. N-Gain, on the other hand, is used to determine an increase in training results. The actual increase in results is the result of N-Gain analysis. It is known that the results of practice are classified as large. As a result, you can see that the numbers before and after the test are compared. T-test (T-test of paired samples) Based on the results of the experiment, we prove that there is a very important comparison. Success can be observed by increasing the effort to practice after the test.